2014
DOI: 10.1111/j.1728-4457.2014.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Blurring Boundaries? Immigration and Exogamous Marriages in Hong Kong

Abstract: This article uses micro‐data from the Hong Kong census since 1991 to report trends in the integration of Chinese residents who were born either in Colonial Hong Kong or in Mainland China. We focus on marital exogamy by nativity for women aged 25–34. From 1991 to 2011, we found an increasing likelihood for Hong Kong native men and Mainland women to be married to one another. This increase reflects cross‐border marriages. Such exogamous marriages were associated with a lower degree of educational homogamy, since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Second, unlike cross-border marriages in other contexts in which the issues of immigration and race/ethnicity are interlocked (Chang, 2016; Erez et al, 2009), husbands and wives in mainland China–Hong Kong cross-border marriages are from the same ethnic Chinese and cultural background (Pong et al, 2014). The co-ethnic background of the cross-border spouses in Hong Kong enables us to examine the nature of cross-border marriage migration without being confounded by the effects of ethnicity.…”
Section: Past Literature and Theoretical Frameworkmentioning
confidence: 99%
“…Second, unlike cross-border marriages in other contexts in which the issues of immigration and race/ethnicity are interlocked (Chang, 2016; Erez et al, 2009), husbands and wives in mainland China–Hong Kong cross-border marriages are from the same ethnic Chinese and cultural background (Pong et al, 2014). The co-ethnic background of the cross-border spouses in Hong Kong enables us to examine the nature of cross-border marriage migration without being confounded by the effects of ethnicity.…”
Section: Past Literature and Theoretical Frameworkmentioning
confidence: 99%
“…The Communist government gradually increased restrictions on individuals leaving China. The border was sealed on both sides in 1980 during negotiations before the Sino–British Joint Declaration (Pong et al., 2014; Pong and Tsang, 2010). Subsequently, deportation of individuals arriving from China was enforced by the British colonial government.…”
Section: The Contextmentioning
confidence: 99%
“…Migrants from mainland China arrived in Hong Kong not only through the 150 daily quota scheme, but also through the “one-way permit.” Most of the immigrants who arrived in Hong Kong through a one-way permit came for the purpose of family reunion. According to Pong et al. (2014), over 760,000 mainland Chinese immigrants arrived in Hong Kong by one-way permit between 1997 and 2012.…”
Section: The Contextmentioning
confidence: 99%
“…Lin and Ma (2008) suggested that Hong Kong men who marry Mainland women tend to be less educated, work in blue-collar jobs, and are about 8 years older than their wives. Adhering to marriage norms of conformal mating, Mainland brides are more likely to have lower educational backgrounds and lower occupational statuses than their husbands (Lin & Ma, 2008), resulting in lower social positions at home and in society (Pong, Post, Ou, & Fok, 2014). In general, households involving a Hong Kong man and a Mainland Chinese wife tend to be economically disadvantaged.…”
Section: Research Sitementioning
confidence: 99%
“…Despite Hong Kong's "handover" to the People's Republic of China in 1997, crossborder marriages and families living between Mainland China and Hong Kong are comparable with transnational families given that a border exists between Mainland China and Hong Kong (Leung & Lee, 2005) and that the Immigration Department of Hong Kong continues to control and regulate the migratory inflow of Mainland Chinese under the Basic Law (Pong et al, 2014). Furthermore, a socio-economic disparity still exists between the two regions due to their uneven paces of socioeconomic development and the disparity in living standards between Mainland China and Hong Kong (Lin & Ma, 2008).…”
Section: Research Sitementioning
confidence: 99%